2022
DOI: 10.2147/rmhp.s370353
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health-Related Quality of Life Among Community-Dwelling Thai Older Adults in Chiang Mai, Northern Thailand

Abstract: Background Population aging has been growing worldwide and Thailand has become an aged society with 20% of its population aged 60 and over. Age-related decline in physical and mental health impacts the health-related quality of life (HRQOL) of older adults. Purpose We aimed to describe the HRQOL of Thai older adults, residing in the community. Methods This cross-sectional survey was part of a Community-Integrated Intermediary Care project (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The investigators involved in the assessment were blinded to the random sampling process. The ADLs were evaluated using Barthel’s ADL index with a Cronbach’s alpha reliability coefficient of 0.90 [ 16 ]. The evaluation form had ten items on the ADL checklist on bathing, dressing, bowel and bladder care, feeding, grooming, climbing stairs, ambulation, transfer, and toilet use.…”
Section: Methodsmentioning
confidence: 99%
“…The investigators involved in the assessment were blinded to the random sampling process. The ADLs were evaluated using Barthel’s ADL index with a Cronbach’s alpha reliability coefficient of 0.90 [ 16 ]. The evaluation form had ten items on the ADL checklist on bathing, dressing, bowel and bladder care, feeding, grooming, climbing stairs, ambulation, transfer, and toilet use.…”
Section: Methodsmentioning
confidence: 99%
“…In this population structure shift, we are facing the big challenges of age-related health issues or increasing ages that come along with health conditions. This phenomenal, no doubt, impact health-related quality of life of senior populations 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to other issues, such as the increasing prevalence of chronic diseases across all ages, shrinking family sizes [ 10 ] and limited access to mental health care [ 15 ], older adults in Indonesia may experience considerable challenges in maintaining their QoL. Previous studies in Indonesia [ 16 , 17 ] and Southeast Asia [ 18 , 19 ] have identified that sociodemographic, physical, and psychological factors may influence QoL among older adults; however, these studies did not explore the influence of these determinants on QoL aspects. Exploration of the association between the determinants and QoL aspects is important to describe the dynamics of QoL and its related factors, and thus may provide recommendations for various disciplines.…”
Section: Introductionmentioning
confidence: 99%